Intraoperative Death: The Untold Stories of Perioperative Teams - Hartley, Heather (Université d'Ottawa / University of Ottawa, 2018)
The Operating Room (OR) is a clinical context in which interprofessional teams surgically intervene with the intention of improving the health of the patients they care for. Despite this, surgery is high risk, invasive and often volatile. The reality is that some patients die in the OR, an outcome which violates the care intention of the clinicians who work there. Using the narrative paradigm, this study explores the stories interprofessional team members shared about caring for patients who died intraoperatively. To appreciate the cultural climate in which these stories were rooted, a literature review of OR culture and theoretical analysis of master narratives was conducted. Using individual interviews, six perioperative clinicians were invited to share their stories: two Registered Nurses, one Registered Practical Nurse, two Surgeons and one Anesthetist. Two analytic approaches were used to authentically capture participant narratives: a narrative thematic approach and structural analysis. The structural analysis revealed the types of stories told—tragedies, romances, comedies and satires—while the thematic perspective elucidated participants’ experiences of intraoperative death and their interpretation of the impact of these experiences. These findings illustrated unique perspectives of intraoperative death, illuminating features which enhanced or deteriorated the experiences for clinicians and their teams. Examining results in tandem with master narratives highlighted prevalent cultural discourses which are held in tension by the clinicians who perpetuate them. Exploring these intersecting elements provides insight into implications for nursing practice, research, education and policy, with particular attention to interprofessional dynamics, staff support, and promoting a culture of resilience.
Keywords: Intraoperative death; Responsibility; Interprofessional dynamics; Traumatic death